Decision Making for a Sustainable and Rentable Maintenance of a TORNADO Gas Turbine based on Fuzzy Logic Concept - Alili, Bachir; Hafaifa, Ahmed; Guemana, Mouloud; Mazouz, Lakhdar (Journal of Vibration Testing and System Dynamics, 2026)
In the modern oil & gas industry ,specifically, in hydrocarbon transportation by pipelines, maintenance decision making for the functional availability of equipment has a major in uence on the profitability of the facilities. In this perspective, this work aims to increase the capacity to monitor the behavior of a TORNADO type gas turbine, installed at an oil pumping station in Hassi R'Mel situated in southern Algeria, with modeling the degradation actions of this machine to make the effective decisions of their maintenance. The maintenance decision support process proposed in this work is based on the concept of fuzzy logic, helps the maintenance operator to choose the most appropriate maintenance actions depending on availability, productivity and quality of the transported oil. This minimizes costs and environmental impact, by ensuring an optimal level of oil transportation, for the monitoring of examined turbine component failures with a sustainable and cost-effective maintenance strategy.